A Comparative Review of Education Policy in Brazil and South Africa: Divergent Trends in Inequality - David James De Villiers; Alethea Cassandra De Villiers (Athens Institute for Education and Research, 2023)
The literature identifies that education policies in Brazil are the backbone of their success in reducing inequality as measured by the GINI index. Since 1994, Brazil is the only BRICS (Brazil, Russia, India, China, South Africa) nation to achieve this. This article presents a comparative study of South Africa and Brazil, and the policies applied towards achieving the Sustainable Development Goals (SDG) of ensuring inclusive and equitable quality education and promoting lifelong learning opportunities for all. Using the analytical framework of the SDG, the strategies of South Africa, and Brazil regarding education are considered in order to identify patterns and themes that can potentially explain the divergence of inequality trends of the two nations. The overarching finding is that subtle differences in education policies perpetuate inequality in South Africa, whereas analogous policies contribute to equality in Brazil. The main contribution of this study is that it locates faults in otherwise well-meaning education policies in South Africa.